2017
DOI: 10.2139/ssrn.3079644
|View full text |Cite
|
Sign up to set email alerts
|

Rohingya Women in Malaysia: Decision-Making and Information Sharing in the Course of Irregular Migration

Abstract: The Robert Schuman Centre for Advanced Studies (RSCAS), created in 1992 and directed by Professor Brigid Laffan, aims to develop inter-disciplinary and comparative research and to promote work on the major issues facing the process of integration and European society.The Centre is home to a large post-doctoral programme and hosts major research programmes and projects, and a range of working groups and ad hoc initiatives. The research agenda is organised around a set of core themes and is continuously evolving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…They began to acknowledge the importance of understanding the stages of these journeys and the decisions asylum-seekers make within their journeys often have significant impacts on their life course (Kuschminder & Waidler, 2019). The past decade of transit migration research showed that migratory decision making for asylum-seekers is not a single process but rather a series of unstable processes that varies over time and space (Düvell et al, 2013;Mallett & Hagen-Zanker, 2018;Schapendonk, 2012;Tazreiter et al, 2017). Each segment of the journey brings new challenges and risks and needs the asylum-seekers to make new adjustments.…”
Section: Asylum-seekers' Decision Making In Transit In a Non-signator...mentioning
confidence: 99%
“…They began to acknowledge the importance of understanding the stages of these journeys and the decisions asylum-seekers make within their journeys often have significant impacts on their life course (Kuschminder & Waidler, 2019). The past decade of transit migration research showed that migratory decision making for asylum-seekers is not a single process but rather a series of unstable processes that varies over time and space (Düvell et al, 2013;Mallett & Hagen-Zanker, 2018;Schapendonk, 2012;Tazreiter et al, 2017). Each segment of the journey brings new challenges and risks and needs the asylum-seekers to make new adjustments.…”
Section: Asylum-seekers' Decision Making In Transit In a Non-signator...mentioning
confidence: 99%
“…In this study, I operationalize irregular return migrants as those who have made one or more trips outside their home country and have returned to the home country, using routes considered dangerous to travelers. In view of the important role information plays to migrants, migration researchers have long identified how everyday word-of-mouth facilitates information sharing (Case, 2012;Pettigrew, Fidel, & Bruce, 2001;Sin & Kim, 2013;Tazreiter, Pickering, & Powell, 2017). Other studies have focused on emerging virtual practices, rapidly transforming social media and network usage, and migration information from search engines (Sin & Kim, 2013;Thulin & Wilhelmson, 2015).…”
Section: Conceptualization Of Access To Migration Information and Infmentioning
confidence: 99%
“…Studies undertaken in the last ten years show that migratory decisionmaking for forcibly displaced migrants is not a single process but rather a series of unstable processes that change over time and space (Schapendonk 2012;Düvell, Wissink and van Eerdewijk 2013;Mallett and Hagen-Zanker 2018;Tazreiter, Pickering and Powell 2017). Journeys in search of safety and protection often tend to not only be lengthy but also fragmented (Collyer 2010).…”
Section: Life On Holdmentioning
confidence: 99%